Ethnography as an Act of Witnessing: Doing Fieldwork on Passion Rituals in the Philippines - Bautista, Julius (Archīum Ateneo, 2014)
Thisarticle juxtaposes two narrative accounts of ethnographic fieldwork on the Passion rituals of Central Luzon in the Philippines. Framed from two distinct cultural and temporal contexts, these narratives highlight the limits and the possibilities of reflexive participant observation in understanding and depicting Filipino religious culture. The authors problematize the assumption that the researcher is the sovereign determinant of fieldwork parameters and local “informants” are merely complicit with the former’s empirical strategies. The act of witnessing, they argue, is a fluid process of exchange conditioned by the expectations and desires of the researcher’s interlocutors and the researcher’s own anxieties over the academic and personal prospects of his or her work.KEYWORDS: Participant Observation • Fieldwork • Passion Rituals • Roman Catholicism • Reflexivity